2018
DOI: 10.1007/s11270-017-3667-z
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella and Fecal Indicator Bacteria Survival in Soils Amended with Poultry Manure

Abstract: Minimizing the risks associated with manure-borne pathogenic microorganisms requires an understanding of microbial survival under realistic field conditions. The objective of this 3-year study was to assess the fate of Salmonella (SALM) and fecal indicator bacteria (FIB), E. coli (EC) and enterococci (ENT), in glacial tillderived soils, after application of poultry manure (PM) to cornfields under chisel-plowed (CP) or no-till (NT) management. From 2010 to 2012, soil samples were obtained each spring at 0-15-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 63 publications
2
29
0
Order By: Relevance
“…Amendment with poultry litter significantly prolonged Salmonella Newport-E survival by 89 days (95% CI = 61.32, 116.02, p ≤ 0.001; Table 2; Figure 4). Overall, these findings are consistent with previous studies (Baloda et al, 2001;Islam et al, 2004a;Holley et al, 2006;You et al, 2006;Nyberg et al, 2010;Ongeng et al, 2011;Hruby et al, 2018;Shah et al, 2019) that reported Salmonella survival increased in soils amended with BSAAO (e.g., poultry litter and bovine manures). For example, You et al (2006) found that addition of bovine manure to agricultural soils increased S. Newport concentrations by as much as 400% within the first 3 days.…”
Section: Salmonella Survived Significantly Longer In Poultry Litter Asupporting
confidence: 92%
See 2 more Smart Citations
“…Amendment with poultry litter significantly prolonged Salmonella Newport-E survival by 89 days (95% CI = 61.32, 116.02, p ≤ 0.001; Table 2; Figure 4). Overall, these findings are consistent with previous studies (Baloda et al, 2001;Islam et al, 2004a;Holley et al, 2006;You et al, 2006;Nyberg et al, 2010;Ongeng et al, 2011;Hruby et al, 2018;Shah et al, 2019) that reported Salmonella survival increased in soils amended with BSAAO (e.g., poultry litter and bovine manures). For example, You et al (2006) found that addition of bovine manure to agricultural soils increased S. Newport concentrations by as much as 400% within the first 3 days.…”
Section: Salmonella Survived Significantly Longer In Poultry Litter Asupporting
confidence: 92%
“…For example, past studies ( Chandler and Craven, 1980 ; Danyluk et al, 2007 ; Underthun et al, 2018 ; Jechalke et al, 2019 ) have suggested that Salmonella can survive for long periods in soils and survival was dependent on soil characteristics (e.g., moisture, composition, and temperature). Specifically, the use of BSAAOs appears to facilitate Salmonella survival ( Baloda et al, 2001 ; Holley et al, 2006 ; You et al, 2006 ; Nyberg et al, 2010 ; Ongeng et al, 2011 ; Hruby et al, 2018 ; Shah et al, 2019 ). For example, a study conducted in Iowa ( Hruby et al, 2018 ) detected Salmonella in soil samples collected from plots amended with poultry litter approximately 1 year after BSAAO application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the presence of Salmonella on parsley was almost lacking in data obtained during this study. These results coincide with the fact that as microbial content in irrigation source increases, the probability of pathogen's incidence on irrigated crops increases simultaneously (Balkhair ; Hruby et al ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, Salmonella can reach agricultural soils via fertilization with pig or poultry manure. Previous reports showed that Salmonella persist in soil for at least 21 days when originating from pig manure (Pornsukarom and Thakur, 2016) and up to one year when originating from poultry manure (Hruby et al, 2018), indicating that soils can act as a long-term Salmonella reservoir. Factors influencing the survival of S. enterica in manure and manure-amended soil were reviewed in Ongeng et al (2015) and include the physical and chemical characteristics of both manure and soil, and also weather and atmospheric conditions, biological interactions, agricultural and livestock management practices, strain variation and physiological age of the cells.…”
Section: Introductionmentioning
confidence: 99%